An Integrated Nutrient Management Approach for Improving Maize (Zea mays L.) Yield: Nutrient Management for Maize Crop - Waseem, Muhammad; Ali, Asghar; Nadeem, Muahammad Ather; Tahir, Muhammad; Ibni Zamir, Muhammad Shahid; Iqbal, Asif; Iqbal, Naveed (Biological Sciences - PJSIR, 2011)
The study of integrated use of chemical fertiliser and compost showed beneficial effects on growth and yield of maize. Plant height, number of grain rows per cob, number of grains per row, number of grains per cob and 1000-grain weight were significantly affected by all the treatments. However, grain yield, biological yield, harvest index and grain-pith ratio were significantly affected by compost and chemical fertiliser alone or in certain combinations. The highest grain yield of 7.18 t/ha was obtained with the application of 25% nitrogen from compost + 75% nitrogen from chemical fertiliser.